Battery preparation process for improving anti-carbon deposition performance of Ni-based composite ceramic fuel electrode
By adjusting the pore structure of the battery support and selecting suitable impregnation materials and processes, covering and protecting large Ni particles, the problem of carbon deposit and deactivation of Ni-based composite ceramic fuel electrodes in carbon and hydrocarbon fuel is solved, and the stability and fuel applicability of the battery are significantly improved.
Patent Information
- Application Number
- CN202411534444.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-04-11
AI Technical Summary
When using hydrocarbon fuel in existing solid oxide fuel cells, Ni-based composite ceramic fuel electrodes are prone to rapid attenuation of battery performance due to carbon deposition.
By adjusting the pore structure of the support body, selecting suitable loading materials, preparing impregnation liquid with high wettability, adjusting the impregnation process and battery testing process, the Ni particles in the anode are coated and protected from carbon deactivation.
It effectively improves the resistance to carbon deposits in carbon and hydrocarbon fuels of Ni-based composite ceramic fuels, extends the stable running time of the battery, and expands the fuel suitability of the fuel cells.
Smart Images

Figure CN119812361A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solid oxide fuel cells, and more specifically, mainly relates to a battery preparation process for improving the carbon deposition resistance of Ni-based composite ceramic fuel electrodes. Background Art
[0002] The technical route of solid oxide fuel cells in generating electricity using hydrogen has matured, and commercial stacks have been able to operate stably for thousands of hours. However, the fuel applicability of the battery has not been fully explored, and the storage and transportation of hydrogen are both challenging, so it is necessary to study the use of hydrocarbon fuels such as methane in solid oxide fuel cells for power generation. When using hydrocarbon fuels, the commonly used Ni-based composite ceramic fuel electrode materials can directly break the CH bonds in the hydrocarbon fuels, and the generated C is integrated into the Ni lattice. As the C content continues to increase, the Ni in the anode is pushed out of the original surface, resulting in the disconnection of the battery conductive network and rapid attenuation of the battery performance. Without changing the commonly used anode materials, in order to inhibit the carbon deposition and deactivation of Ni particles in the support in hydrocarbon fuels, it is necessary to modify and protect them to a certain extent, including two technical paths: one is to add an additional reforming layer outside the anode support, pre-reform the hydrocarbon fuel into CO and H2, and then enter the battery for power generation; the other is to impregnate and modify the large particles of Ni in the support to achieve in-situ reforming conversion and efficient power generation.
[0003] Due to the limited load capacity of the first approach, the supply of hydrocarbon fuel needs to be precisely controlled according to the amount of external load of the battery to avoid reducing the utilization rate of the fuel gas; at the same time, due to the insufficient electronic conductivity of the loaded material, the traditional current collection method cannot effectively collect the electrons conducted by the anode support, and a new current collection method is needed to avoid the additional reforming layer. The great influence on the battery ohmic impedance and performance will affect the sealing of the battery. Relatively speaking, the second approach will not change the overall structure of the battery, nor does it require a complex and precise new current collection method. It is a process path with higher application prospects and value. At the same time, in the second approach, in order to make the impregnation solution reach the interface between the anode functional layer and the electrolyte and impregnate the large Ni particles in the coated anode as much as possible, in addition to reducing the surface tension of the impregnation solution and improving the wettability of the impregnation solution and the electrode, it is also necessary to increase the porosity of the battery support and perform impregnation after the initial reduction of the battery. On the one hand, the surface tension of the impregnation liquid is the determining factor for the degree of dispersion of the impregnation liquid on the surface of the support. The smaller the surface tension, the smaller the wetting angle between the impregnation liquid and the substrate, and the more uniform the coating of the impregnated particles. On the other hand, the deflection and porosity of the substrate affect the dynamic penetration of the impregnation liquid in the thicker battery support: Generally speaking, the smaller the deflection of the substrate and the higher the porosity, the greater the penetration depth of the impregnation liquid and the better the dispersion. In addition, some external conditions such as temperature, vacuum, oscillation stirring, and ultrasound also have a great influence on the impregnation effect.
[0004] At the same time, the material for impregnation and coating Ni needs to meet certain conditions, namely high electronic conductivity, oxygen ion conductivity, good adsorption capacity for reaction gases and sufficient catalytic activity. CeO2 material has high oxygen ion conductivity, and doping with active metals and then in-situ precipitation can improve its catalytic activity; active metal-doped perovskite materials have high catalytic activity and stability after in-situ precipitation; alkaline earth metals and transition metal oxides have high adsorption capacity for reactants and intermediates of reforming reactions (such as H2O, CO2, OH-, etc.), which can improve the oxygen-carbon ratio of the local electrode and inhibit carbon deposition.
[0005] In summary, how to adjust the three-dimensional structure of the battery support, select suitable impregnation materials, improve the impregnation process and control the battery testing conditions are crucial to improving the anti-carbon deposition performance of Ni-based composite ceramic fuel electrodes when using hydrocarbon fuels for power generation. Summary of the invention
[0006] In order to solve the problem that the existing SOFC cannot use hydrocarbon fuels to generate electricity, the present invention provides a battery preparation process for improving the carbon deposition resistance of Ni-based composite ceramic fuel electrodes, the purpose of which is to coat and protect the large Ni particles in the anode by adjusting the pore structure of the support, selecting suitable loading materials, preparing an impregnation solution with high wettability, adjusting the impregnation process and the battery testing process, thereby solving the problem of carbon deposition and deactivation of the battery in hydrocarbon fuels.
[0007] To achieve the above object, the present invention is implemented through the following technical solutions:
[0008] In a first aspect, the present invention provides a battery preparation process for improving Ni-based composite ceramic fuel electrodes, the method comprising the following steps:
[0009] (1) Preparation of macroporous battery: PMMA, PVB, PS organic matter is selected as a new type of pore-forming agent, and a macroporous Ni-GDC support is prepared by tape casting, or a Ni-GDC support with vertical channels is prepared by phase conversion method. After the support is pre-sintered, the Ni-GDC anode functional layer, GDC electrolyte, and La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ The (LSCF)-GDC air electrode was screen-printed and sintered to obtain a full cell;
[0010] (2) Selection of impregnation materials: Select materials that can maintain a stable phase structure in a reducing atmosphere, such as Gd / Sm-doped CeO2 materials and Cr-based, Mn-based, and Ti-based perovskite materials, and dope active metals Ni, Fe, and Ru and then precipitate them in situ as catalytic sites; or select oxides such as Pr6O that have the ability to adsorb water and carbon dioxide. 11 , MgO, increases the oxygen-carbon ratio at the three-phase interface and inhibits carbon deposition;
[0011] (3) Preparation of impregnation solution: isopropanol or anhydrous ethanol with a small surface tension is selected as the solvent, and a complexing agent and a chelating agent are added after the metal nitrate is completely dissolved, and then an appropriate amount of a surfactant is added to reduce the surface tension of the impregnation solution, and a series of concentrations of impregnation solutions are prepared;
[0012] (4) Impregnation process: Use a pipette to quantitatively transfer 10-15 μl of impregnation solution and drip it onto the outer surface of the fuel electrode. Heat it to promote impregnation. After it is completely dried, calcine it in a muffle furnace / atmosphere furnace to remove organic matter in the impregnation solution and maintain a certain bonding strength between the impregnated material and the substrate. Repeat this step 3-5 times;
[0013] (5) Full cell test: After the cell is fully reduced under H2 conditions, the temperature is cooled to 550-650°C and a hydrocarbon fuel (3 vol% H2O) or dry / wet reformed gas in different proportions is introduced to test the electrochemical performance and stability.
[0014] Preferably, when preparing the support, the particle size of the pore-forming agents PMMA, PVB and PS balls is controlled at 10-50 microns, and the mass proportion of the pore-forming agents is controlled at 10-30% of the total mass of the support (NiO+GDC) powder.
[0015] Further preferably, the pore-forming agent is polymethyl methacrylate (PMMA), the particle size can be selected to be 10 microns or 15 microns, and the mass addition ratio of the pore-forming agent is 10-20% of the total mass of the support (NiO+GDC);
[0016] Preferably, the impregnation material is selected from (Ce 0.9 G 0.1 ) 1-x (NiFeRu) x O 2-δ or (La 0.9 Sr 0.1 ) 1-y Cr 1-x (FeNiRu) x O 3-δ or (La 0.8 Ca 0.2 ) 1-y Ti 1-x (FeNiRu) x O 3-δ or (Pr 0.8 Ca 0.2 ) 1-y Mn 1-x (FeNiRu) x O 3-δ or Pr6O 11 Or any one of MgO, wherein x is 0-0.2, y is 0-0.2, and x and y are adjusted according to the stability of the perovskite phase after doping and the amount of precipitated metal;
[0017] Further preferably, the impregnated material can be selected as (Ce 0.9 G 0.1 ) 0.9 (Ni 1 / 3 Fe 1 / 3 Ru 1 / 3 ) 0.1 O 2-δ , or (La 0.9 Sr 0.1 ) 0.9 Cr 0.8 Fe0.1 Ni 0.1 O 3-δ , or (La 0.8 Ca 0.2 ) 0.8 Ti 0.8 Ni 0.2 O 3-δ , or (Pr 0.8 Ca 0.2 ) 0.8 Mn 0.8 Ni 0.1 Ru 0.1 O 3-δ , or Pr6O 11 or MgO;
[0018] Preferably, the solvent selected for the preparation of the impregnation solution is a mixture of isopropanol and deionized water; in addition, when the metal nitrate can be dissolved in anhydrous ethanol, anhydrous ethanol is used as the solvent, and the concentration of the impregnation solution is 0.1-0.5M;
[0019] Further preferably, the impregnation solution solvent is a mixture of isopropanol and deionized water, with a volume ratio of (2:8)-(1:1, the volume ratio of isopropanol is increased under the premise that the metal nitrate can be dissolved;
[0020] Further preferably, the complexing agent and chelating agent used in the impregnation solution configuration is a combination of citric acid monohydrate and ethylenediaminetetraacetic acid, or ethylene glycol solution, or glycine; the molar ratio of the complexing agent and chelating agent to the total metal ions is (1:1) to (2:1); when a combination of citric acid monohydrate and ethylenediaminetetraacetic acid is used, the molar ratio of citric acid monohydrate to ethylenediaminetetraacetic acid is 1.5:1;
[0021] Preferably, the surfactant used in the impregnation liquid is polyvinyl butyral (PVB), or Triton X-100, or hydroxyethyl phenethyl ether, and the quality is controlled to be 10-20wt% of the impregnation material;
[0022] Preferably, during the impregnation liquid injection process, the battery is placed in a constant temperature oven at 80°C, 10-15 microliters of the impregnation liquid is dripped each time, and after being fully dried, the battery is placed in a 300-400°C atmosphere furnace for pre-burning for 1-2 hours, and the heating and cooling rates during this process do not exceed 1°C / min, and this step is repeated 3-5 times;
[0023] Preferably, before testing, the battery is heated to 500°C in a 5% H2-N2 atmosphere, and the heating rate is reduced to 1°C / min to prevent the battery from deforming too quickly and causing the electrolyte to crack; after heating to 750°C, switch to pure H2 for reduction and precipitation for 2-4 hours, and finally cool to 550-650°C for electrochemical performance testing of hydrocarbon fuels;
[0024] Preferably, when the battery is tested, the fuel gas may be water-removed CH4 (3 vol% H2O), wet reformed gas with different ratios of CH4 and H2O, or dry reformed gas with different ratios of CH4 and CO2;
[0025] Further preferably, the test conditions are humidified methane (3 vol% H2O), or 1:1 CH4-CO2 / H2O reformed gas, and the total fuel flow rate is controlled at 30-50 mL / min.
[0026] In a second aspect, the present invention provides a carbon deposition resistant fuel electrode prepared by the above-mentioned battery preparation process for improving the anti-carbon deposition performance of Ni-based composite ceramic fuel electrodes. The carbon deposition resistant fuel electrode is used in the preparation and testing of solid oxide fuel cells that use hydrocarbon fuels to generate electricity.
[0027] In a third aspect, the present invention provides a battery prepared by the above-mentioned battery preparation process for improving the anti-carbon deposition performance of Ni-based composite ceramic fuel electrodes.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention provides a solid oxide fuel cell prepared by the method described above, wherein the cell comprises a fuel electrode functional layer supported by an anti-carbon deposition material and a support. Through this technical solution, the anti-carbon deposition ability of the fuel electrode in hydrocarbon fuels is improved, and the fuel applicability of the solid oxide fuel cell is expanded.
[0030] The Ni skeleton in the battery support and the functional layer prepared by the present invention is uniformly coated, which avoids the occurrence of carbon deposition in hydrocarbon fuels, effectively improves the stability of the solid oxide fuel cell when generating electricity using hydrocarbon fuels, and expands the fuel applicability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the operation of impregnation modification for batteries.
[0032] Figure 3 The figure is a linear graph comparing the discharge stability test results of the unimpregnated battery and the impregnated battery in the constant current mode at 600°C and in wet CH4 fuel.
[0033] Figure 2 The microscopic morphology of the unimpregnated battery and the improved impregnated battery after long-term testing at 600°C in wet CH4 fuel; Figure 2 (a) and Figure 2 (c) is the microscopic morphology of the unimpregnated fuel electrode after 50h testing; Figure 2 (b) and Figure 2(d) shows the microstructure of the impregnated improved fuel electrode after 100h discharge test. DETAILED DESCRIPTION
[0034] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.
[0035] Example 1
[0036] This embodiment provides a battery for improving the carbon deposition resistance of a Ni-based composite ceramic fuel electrode, and the preparation process thereof comprises the following steps:
[0037] 1. Preparation of batteries
[0038] In this embodiment, the battery matrix is prepared by the commonly used process of tape casting + pre-sintering + screen printing + high-temperature co-firing. The pore-forming agent in the battery support is selected to be a mixture of PMMA with a particle size of 15 microns and 10 microns, and the mass of the pore-forming agent accounts for 15% of the total mass of NiO and GDC. The tape is air-dried and degreased, and then pre-fired at 1150°C for 3 hours to give it a certain mechanical strength; after screen-printing the Ni-GDC functional layer and GDC electrolyte, the electrolyte is sintered and compacted by co-firing at 1550°C for 6 hours. Select LSCF-GDC air electrode material with excellent performance in the low temperature range, screen-print the oxygen electrode material, and sinter it at 900°C to give it a certain bonding strength with the electrolyte.
[0039] 2. Preparation of impregnation solution
[0040] Impregnation material selection (Ce 0.9 G 0.1 ) 0.9 (NiFeRu) 0.1 O 2-δ Materials. Accurately weigh the metal nitrate and dissolve it in a mixed solvent of isopropanol and deionized water, wherein the volume ratio of isopropanol to deionized water is 1:1. Then weigh citric acid monohydrate and ethylenediaminetetraacetic acid as complexing agents and chelating agents according to the molar ratio of total metal ions: citric acid monohydrate: ethylenediaminetetraacetic acid of 1:1.5:1, adjust the pH of the solution to 7-8 with ammonia water, and stir thoroughly. Finally, add 20wt% of the impregnation material of Triton X-100 as a surfactant to reduce the surface tension of the solution and enhance the penetration ability of the solution. The concentration of the impregnation solution is 0.3M.
[0041] 3. Battery reduction and solution immersion
[0042] The battery was slowly heated to 800°C at a heating rate of 2°C / min in a 5% H2-N2 atmosphere and kept warm for 12 hours to fully reduce the Ni in the battery support and the anode functional layer, increase the battery porosity, and provide conditions for subsequent impregnation. Then, 10 microliters of impregnation solution was quantitatively transferred with a pipette and dripped onto the outer surface of the battery support. At the same time, it was placed in an 80°C oven to dry, and then calcined at 300°C in a muffle furnace for 1 hour to remove organic matter in the impregnation solution. The heating and cooling rates during calcination were set to 1°C / min to prevent the battery from cracking. This step was repeated 5 times. Schematic diagram of battery impregnation improvement, as shown in Figure 1 shown.
[0043] 4. Battery test
[0044] The prepared battery was sealed and heated to 500°C at a heating rate of 2°C / min in a 5% H2-N2 atmosphere. The heating rate was then reduced to 1°C / min, and the temperature was slowly raised to 750°C, and the battery was switched to pure H2 reduction for 2-4 hours. Then, a methane fuel with water was introduced at 600°C for long-term discharge performance testing, and the methane flow rate was controlled at 40mL / min. The unimpregnated and impregnated modified batteries were tested at 600°C and 400mA / cm 2 The discharge stability test in constant current mode is as follows Figure 3 As shown, the microscopic morphology of the battery after the test is as follows Figure 2 shown.
[0045] Example 2
[0046] This embodiment provides a battery for improving the carbon deposition resistance of a Ni-based composite ceramic fuel electrode, and the preparation process thereof comprises the following steps:
[0047] 1. Preparation of batteries
[0048] The battery preparation process and reduction process used in this embodiment are consistent with those in Embodiment 1.
[0049] 2. Preparation of impregnation solution
[0050] Select MgO as the impregnation material. Accurately weigh Mg(NO3)2·6H2O and dissolve it in anhydrous ethanol. 2+ The molar ratio of ethylene glycol is 1:1.5. Ethylene glycol is weighed to provide -OH to participate in the complexation reaction and improve the stability of the gel. Finally, 20wt% of polyvinyl butyral (PVB) of the impregnation material is added as a surfactant to reduce the surface tension of the solution and improve the penetration ability of the solution. The concentration of the impregnation solution is 0.5M.
[0051] 3. Battery reduction and solution immersion
[0052] The battery reduction process is the same as that in Example 1. Then, 10 microliters of the impregnation solution is quantitatively transferred with a pipette and dripped onto the outer surface of the battery support body, and then placed in an 80°C oven for drying, and then calcined at 400°C in an atmosphere furnace for 1 hour to remove organic matter in the impregnation solution and decompose magnesium nitrate. The heating and cooling rates during calcination are set to 1°C / min to prevent the battery from cracking, and 5% H2-N2 atmosphere is used as a protective gas. This step is repeated 5 times.
[0053] 4. Battery test
[0054] The prepared battery was sealed and heated to 500°C at a heating rate of 2°C / min in a 5% H2-N2 atmosphere, then the heating rate was reduced to 1°C / min, slowly heated to 750°C, and switched to pure H2 reduction battery for 2-4 hours. Then, wet reforming gas with a ratio of CH4:H2O=1:1 was introduced, the water vapor content was set by adjusting the temperature of the water vapor generator, the total amount of fuel gas was controlled at 40mL / min, and a long-term discharge stability test was performed at 600°C.
[0055] Example 3
[0056] This embodiment provides a battery for improving the carbon deposition resistance of a Ni-based composite ceramic fuel electrode, and the preparation process thereof comprises the following steps:
[0057] 1. Preparation of batteries
[0058] In this embodiment, the phase conversion method is used to prepare a Ni-GDC battery support with vertical channels. N-methylpyrrolidone (NMP) is selected as the solvent, polyethersulfone (PESf) with a mass of 25% of the solvent is added as the polymer material, and polyvinylpyrrolidone (PVP) with a total mass of 2% of NMP and PESf is added as an additive. The glass rod is stirred evenly at 80°C and allowed to stand to form a uniform and transparent polymer solution. Subsequently, NiO and GDC powders weighed in a mass ratio of 3:2 (the total mass is equal to the polymer solution) are added, placed in a ball mill at a speed of 300rpm for 12 hours to obtain a polymer slurry, vacuum degassing for 20 minutes, and then tape-casting is performed. After air drying, a disc with a diameter of 16mm is punched out with a mold to obtain an anode green body. The pre-calcination procedure in Example 1 was followed to remove organic matter and give the substrate a certain mechanical strength. The Ni-GDC functional layer and the GDC electrolyte layer were then screen-printed in sequence, and the mixture was calcined at 1550°C for 6 hours to obtain a dense electrolyte. The air electrode material was then prepared according to the steps in Example 1.
[0059] 2. Preparation of impregnation solution
[0060] Impregnation material selection (La 0.9 Sr 0.1 ) 0.9Cr 0.8 Fe 0.1 Ni 0.1 O 3-δ . Accurately weigh the metal nitrate and dissolve it in a mixed solvent of isopropanol and deionized water in a volume ratio of 1:1. Then weigh monohydrated citric acid as a complexing agent according to the molar ratio of the total metal salt ions to monohydrated citric acid of 1:1.5. Finally, add 20wt% of polyvinyl butyral (PVB) as a surfactant to reduce the surface tension of the solution and improve the penetration ability of the solution. The concentration of the impregnation solution is 0.1M.
[0061] 3. Battery reduction and solution immersion
[0062] The battery reduction process is the same as that in Example 1. Then, 10 microliters of the impregnation solution is quantitatively transferred with a pipette and dripped onto the outer surface of the battery support body, and then placed in an 80°C oven for drying, and then calcined at 400°C in an atmosphere furnace for 1 hour to remove organic matter in the impregnation solution. The heating and cooling rates during calcination are set to 1°C / min to prevent the battery from cracking, and a 5% H2-N2 atmosphere is used as a protective gas. This step is repeated 3 times. After the last impregnation, the battery is heated to 900°C in a 5% H2-N2 atmosphere for 2 hours to phase the impregnated perovskite material and precipitate nano-active metal particles.
[0063] 4. Battery test
[0064] The test conditions are consistent with those in Example 1.
[0065] Comparative Example 1
[0066] This comparative example is similar to Example 1, except that the steps related to the impregnation improvement are omitted. The battery is tested for long-term discharge performance using the test conditions of Example 1. The battery discharge stability test in constant current mode at 600°C in wet CH4 fuel is as follows: Figure 3 shown.
[0067] Figure 3 The figure is a comparison of the discharge stability test results of the unimpregnated battery prepared in Comparative Example 1 and the impregnated battery prepared in Example 1 in the constant current mode at 600°C in wet CH4 fuel. Figure 3 It can be seen that the unimpregnated battery prepared in Comparative Example 1 continued to decay within 50 hours, while the impregnated battery prepared in Example 1 was able to operate stably for more than 100 hours, with the voltage only decaying from 0.76V to 0.75V.
[0068] Morphological observation of battery after long-term testing
[0069] Electrochemical performance test (long-term discharge performance test) After the test, the microscopic morphology of the unimpregnated battery prepared in comparative example 1 and the impregnated improved battery prepared in example 1 was tested, and the morphology and carbon deposition of the anode support were observed by SEM to evaluate the protective effect of the impregnated material and the anti-carbon deposition ability of the improved anode. Among them, the unimpregnated battery prepared in comparative example 1 is the morphology after 50h test, and the impregnated improved battery prepared in example 1 is the morphology after 100h test. The results are as follows: Figure 2 shown.
[0070] Figure 2 The following is a comparison of the microscopic morphology of the unimpregnated battery prepared in Comparative Example 1 and the improved impregnated battery prepared in Example 1 after long-term testing at 600°C in wet CH4 fuel. Figure 2 (a) and Figure 2 (c) It can be seen that after 50h of testing, the Ni skeleton in the support of the unimpregnated battery prepared in Comparative Example 1 was "dismembered" by the continuous accumulation of C. This is because the C generated by the cracking of CH4 is integrated into the Ni lattice, and the continuous accumulation pushes the Ni particles away from the original surface, eventually leading to the cracking of large Ni particles and the destruction of the battery conductive network; Figure 2 (b) and Figure 2 (d) It can be seen that after the battery impregnated with protective materials was tested in wet CH4 for 100 h, the surface of the supporting Ni particles was evenly coated with the modified material, and the large-particle Ni matrix still maintained its original morphology.
[0071] The above-mentioned embodiments only express the specific implementation of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A battery preparation process for improving the carbon deposition resistance of Ni-based composite ceramic fuel electrodes, characterized in that: The method comprises the following steps: (1) Preparation of macroporous battery: at least one of polymethyl methacrylate (PMMA), polyvinyl butyral (PVB), and polystyrene (PS) is selected as a pore former, and the pore former is mixed with NiO and GDC powder to prepare a Ni-GDC support with a porosity of 20-30% (before reduction), or a Ni-GDC support with vertical channels is prepared by a phase conversion method. After the support is pre-sintered, a functional layer, an electrolyte, and an oxygen electrode layer are sequentially prepared on one side to obtain a full battery; (2) Selection of impregnation materials: Gd doped with active metals Ni, Fe, and Ru 0.1 Ce 0.9 O 1.95 (GDC); or Cr-based, Mn-based, Ti-based perovskite materials doped with active metals Ni, Fe, and Ru, which precipitate active metals as catalytic sites during the battery reduction process, while the abundant oxygen vacancies in the matrix material provide a fast channel for oxygen transfer; or Pr6O 11 , MgO oxide, which increases the oxygen-carbon ratio in the reaction area and inhibits the occurrence of battery carbon deposition; (3) Preparation of impregnation solution: selecting a combination of isopropanol + deionized water or anhydrous ethanol with a small surface tension as a solvent, dissolving the impregnation material of step (2), preparing an impregnation solution with a concentration of 0.1-0.5M, adding glycine, or ethylene glycol, or a combination of citric acid + ethylenediaminetetraacetic acid as a complexing agent and chelating agent, and then adding a surfactant to further reduce the surface tension of the solution; (4) Impregnation liquid injection: After the battery prepared in step (1) is fully reduced at 800°C, 10-15 μl of the impregnation liquid is quantitatively pipetted each time using a pipette and dripped onto the outer surface of the support body, while keeping the temperature at 80°C to promote the penetration of the impregnation liquid. After drying, calcination is performed, and this step is repeated; (5) Battery test: After the battery is reduced in pure H2 at 750°C for 2-4 hours, water-permeated CH4 or CH4-CO2 dry reforming gas or CH4-H2O wet reforming gas in different ratios are introduced to test the long-term stability of the battery in the temperature range of 550-650°C.
2. A battery preparation process for improving the carbon deposition resistance of Ni-based composite ceramic fuel electrodes according to claim 1, characterized in that: The particle sizes of the pore-forming agents PMMA, PVB and PS balls during the preparation of the support are controlled at 10-50 microns, and the mass proportion of the pore-forming agents is controlled at 10-30% of the total mass of the support powder (NiO+GDC).
3. A battery preparation process for improving the carbon deposition resistance of Ni-based composite ceramic fuel electrodes according to claim 1, characterized in that: The impregnation material selection (Ce 0.9 G 0.1 ) 1-x (NiFeRu) x O 2-δ or (La 0.9 Sr 0.1 ) 1-y Cr 1-x (FeNiRu) x O 3-δ or (La 0.8 Ca 0.2 ) 1-y Ti 1-x (FeNiRu) x O 3-δ or (Pr 0.8 Ca 0.2 ) 1-y Mn 1-x (FeNiRu) x O 3-δ or Pr6O 11 Or any one of MgO, wherein x is 0-0.2, y is 0-0.2, and x and y are adjusted according to the stability of the perovskite phase after doping and the amount of precipitated metal.
4. A battery preparation process for improving the carbon deposition resistance of Ni-based composite ceramic fuel electrodes according to claim 1, characterized in that: The solvent selected for the preparation of the impregnation solution is a mixture of isopropanol and deionized water, with a volume ratio of (2:8)-(1:1); or when the metal nitrate can be dissolved in anhydrous ethanol, anhydrous ethanol is selected as the solvent, and the concentration of the impregnation solution is 0.1-0.5M.
5. A battery preparation process for improving the carbon deposition resistance of Ni-based composite ceramic fuel electrodes according to claim 1, characterized in that: The complexing agent and chelating agent of the impregnation solution are selected from glycine, ethylene glycol, or a mixture of citric acid and ethylenediaminetetraacetic acid, which are added to the total metal ions in a molar ratio of (1:1)-(2:1) (wherein, The molar ratio of citric acid to ethylenediaminetetraacetic acid is 1.5:1); the selected surfactants are polyvinyl butyral (PVB), Triton X-100, and hydroxyethyl phenethyl ether, and the quality is controlled at 10-20wt% of the impregnated material.
6. A battery preparation process for improving the carbon deposition resistance of Ni-based composite ceramic fuel electrodes according to claim 1, characterized in that: During the impregnation liquid injection process, the battery (diameter of about 13 mm, thickness of about 0.8 mm) is placed in a constant temperature oven at 80°C, and 10-15 μl of the impregnation liquid is dripped each time. After sufficient drying, the battery is placed in a 300-400°C atmosphere furnace and calcined for 1-2 hours. During this process, the heating and cooling rates do not exceed 1°C / min, and this step is repeated 3-5 times.
7. A battery preparation process for improving the carbon deposition resistance of Ni-based composite ceramic fuel electrodes according to claim 1, characterized in that: Before testing, the battery was heated to 500°C in a 5% H2-N2 atmosphere, then the heating rate was switched to <1°C / min and heated to 750°C, then switched to pure H2 for reduction for 2-4 hours, and finally the electrochemical performance of hydrocarbon fuel was tested.
8. The battery preparation process for improving the carbon deposition resistance of Ni-based composite ceramic fuel electrodes according to claim 1, characterized in that: When the battery is tested, the fuel gas can be CH4 that has been hydrated, wet reformed gas of CH4 and H2O, or dry reformed gas of CH4 and CO2, and the gas flow rate is controlled at 30-40 mL / min.
9. The anti-carbon deposition fuel electrode and battery prepared by the battery preparation process for improving the anti-carbon deposition performance of Ni-based composite ceramic fuel electrode according to any one of claims 1 to 8, characterized in that: Applied to the preparation and testing of solid oxide fuel cells that use hydrocarbon fuels to generate electricity.
Citation Information
Cited By
Method for directionally loading catalyst on Ni-based composite ceramic fuel electrode
CN121054713A